2019
DOI: 10.1111/1747-0080.12547
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition risk and mortality in older oncology patients: An exploratory study

Abstract: Aim: The primary aim of this analysis was to identify if two standard measures incorporated into the comprehensive geriatric assessment; specifically, malnutrition risk and body mass index (BMI), could predict 12-month mortality in older patients with solid tumours. The secondary aim was to evaluate if malnutrition risk and BMI were associated with chemotherapy outcomes (discontinuation/modification of treatment) in older patients with solid tumours. Methods: Older patients (aged ≥70 years) with solid cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The incidence of cancer is increasing, primarily due to the ageing population. The estimated number of new cases in people aged 65 and older is expected to increase from 9.95 million in 2020 to 18.6 million in 2040 (Botero et al, 2019;World Health Organization, 2021). People with cancer aged 65 and older are predisposed to a range of comorbidities, including hypertension, heart disease, dyslipidemia and diabetes (Australian Institute of Health and Welfare, 2021; Davis et al, 2011).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of cancer is increasing, primarily due to the ageing population. The estimated number of new cases in people aged 65 and older is expected to increase from 9.95 million in 2020 to 18.6 million in 2040 (Botero et al, 2019;World Health Organization, 2021). People with cancer aged 65 and older are predisposed to a range of comorbidities, including hypertension, heart disease, dyslipidemia and diabetes (Australian Institute of Health and Welfare, 2021; Davis et al, 2011).…”
Section: Reviewmentioning
confidence: 99%
“…Malnutrition is known to be one of the most serious comorbidities that influence the trajectory of cancer-related symptoms (Botero et al, 2019). Malnutrition or undernutrition is defined as "a state resulting from lack of intake or uptake of nutrition that leads to altered body composition and body cell mass leading to diminished physical and mental function and impaired clinical outcomes from disease" (European Society for Clinical Nutrition and Metabolism, 2021, p. 51).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Zükeran et al, it was observed that frailty is higher in older patients at risk of malnutrition [16]. In another study with older patients with cancer, a close relationship was found between malnutrition risk and 12-month mortality [17]. Therefore, older patients with cancer should be carefully evaluated for malnutrition risk and a systematic approach is necessary.…”
Section: Introductıonmentioning
confidence: 99%
“…The study brings into focus past dietary patterns affecting malnourished patients on admission. Botero et al 11 undertook an exploratory study of 74 oncology patients to identify if adding malnutrition risk and body mass index (BMI) could predict 12‐month mortality. A secondary aim of this study was to evaluate if malnutrition risk and BMI were associated with chemotherapy outcomes.…”
mentioning
confidence: 99%